22nd AIAA Computational Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-3208
|View full text |Cite
|
Sign up to set email alerts
|

A Priori Analysis of a Compressible Flamelet Model using RANS Data for a Dual-Mode Scramjet Combustor

Abstract: In an effort to make large eddy simulation of hydrocarbon-fueled scramjet combustors more computationally accessible using realistic chemical reaction mechanisms, a compressible flamelet/progress variable (FPV) model was proposed that extends current FPV model formulations to high-speed, compressible flows. Development of this model relied on observations garnered from an a priori analysis of the Reynolds-Averaged Navier-Stokes (RANS) data obtained for the Hypersonic International Flight Research and Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…This clearly illustrates the need to examine alternative methods that accurately parameterize complex chemistry with only a limited number of scalars. Our group is currently examining a flamelet-based strategy [34,35] to address this issue.…”
Section: Combusting Resultsmentioning
confidence: 99%
“…This clearly illustrates the need to examine alternative methods that accurately parameterize complex chemistry with only a limited number of scalars. Our group is currently examining a flamelet-based strategy [34,35] to address this issue.…”
Section: Combusting Resultsmentioning
confidence: 99%
“…Their a priori analysis showed relatively minor differences using this approach compared to the full expression [33]. In our simulations, however, we found that this approximation is not sufficiently accurate, resulting in spurious temperature variations and poor numerical stability.…”
Section: Evm-les Implementationmentioning
confidence: 66%
“…This clearly illustrates the need to find alternative methods to accurately parametrize the complex chemistry with only a limited number of scalars. Our group is currently examining a flamelet-based strategy 30,31 to address this issue.…”
Section: Summary and Future Workmentioning
confidence: 99%